Impact of privacy risk on facebook fan page loyalty: empirical study of facebook users - Sudarshana, S.A.; Kumaradeepan, V. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
With the rapid expansion of social networking sites, researchers arechallenged to understand how privacy risk has effect on customer loyalty in fan pages. The purpose of this paper is toidentify the impact of privacy risk on Facebook fan page loyalty in order to promote the creation of affective links and long-term relationships with users. The impact of privacy risk on loyalty to fan pages was tested through structural equation modelling techniques.The sample consisted of 300 Sri Lankan Facebook users. Privacy risk has not been tested in previous studies regarding Facebook page loyalty. According to the analysis, it can be concluded that there is impact of Privacy Risk on Facebook page loyalty. This research enables managers to know what aspects to highlight in their communication and promotion strategies to increase fan page use and privacy risk policies. Research findingsshow managers and companies that Facebook fan page content should provide valuable information. Practical recommendations to reinforce privacy risk on Facebook fan pages are also provided. The proposed model reveals not how privacy risk involves in social media marketing, especially on facebook platform. The study and the proposed model may be used as a starting and introduction point for further Facebook marketing related research.
Keywords: Privacy Risk; Loyalty; Social Media; Facebook; Facebook Fan Pages